Preoperative distraction in children: hand-held videogames vs clown therapy - M. Messina; F. Molinaro; D. Meucci; R. Angotti; L. Giuntini; E. Cerchia; A.L. Bulotta; E. Brandigi (PAGEPress Publications, 2014)
Anxiety in children undergoing surgery is characterized by feelings of tension, apprehension, nervousness and fear which may manifest differently. Postoperative behavioural changes such as nocturnal enuresis, feeding disorders, apathy, and sleep disturbances may stem from postoperative anxiety. Some Authors pointed out that over 60% of children undergoing surgery are prone to developing behavioural alterations 2 weeks after surgery. Variables such as age, temperament and anxiety both in children and parents are considered predictors of such changes.1 Studies were published describing how psycho-behavioural interventions based on play, learning and entertainment in preparing children for surgery, may reduce preoperative anxiety. Clown-therapy is applied in the most important paediatric facilities and has proved to diminish children's emotional distress and sufferance, as well as consumption of both analgesics and sedatives and to facilitate the achievement of therapeutic goals. The aim of our study was to evaluate the efficacy of clown-therapy during the child's hospital stay, with a view to optimizing treatment and care, preventing behavioural alterations and enhancing the child's overall life quality.